Gender Differences in the Clinical Presentation of Cluster Headache: A Role for Sexual Hormones? - Allena, Marta; De Icco, Roberto; Sances, Grazia; Ahmad, Lara; Putortì, Alessia; Pucci, Ennio; Greco, Rosaria; Tassorelli, Cristina (Frontiers in Neurology, 2019)
Introduction Cluster Headache (CH) is a very well characterized primary headache disorder. CH mostly affects men but an increasing percentage of women also suffers from this disease. Available data on gender-related differences in CH are very scarce and partly discordant. The aim of this manuscript is the careful definition of clinical profile of CH between the sexes. Material and methods Retrospective analysis of a clinical database of CH patients diagnosed and followed at the Pavia Headache Center between September 2016 and December 2018. Results We collected data from 250 CH patients, 163 males (mean age 41.46+10.37years) and 87 females (mean age 42.24+11.95 years). The mean age of CH onset was similar for both sexes but surprisingly the onset of disease often coincided with periods of abrupt fluctuations of sexual hormone levels (menarche, post-partum, menopause). Women had a longer mean attack duration (p=0.004) than men, without symptomatic treatment, and tended to have more attacks per day (p=0.053). Nausea and osmophobia were reported more frequently by women (p=0.048, p=0.037, respectively). Autonomic associated symptoms were almost equally prevalent in women and men, with the exception of ptosis (predominant in female) and enlarged temporal artery and nasal congestion (both more expressed in men). Concomitant thyroid diseases (23% vs 1.8%, p=0.001) and psychiatric disorders (17.2% vs 9.2%, p= 0.04) mostly occur in women than men. Snoring in sleep and smoking habit is more frequent in men: 53.4% vs 19.5% (p=0.00) and 67.5% vs 49.4% (p=0.005), respectively. Conclusion Despite an overall similar clinical presentation of cluster headache in both sexes, in women some features seem to overlap with migraine, as suggested by existing literature: the prevalence of “migrainous” associated symptoms during attacks, the more robust family history of migraine, the association of CH onset with hormonal changes, the longer duration of CH attacks and the more widespread distribution of pain. These our findings may have a relevance in terms of a pathophysiological role of sexual hormones so far unexplored in CH. Further investigations along this line may lead to an improved global management of the disease, from the diagnosis to new gender-related therapeutic strategies.